Aegaron, Ägypten: Ancient Egyptian Architecture Online (AEgArOn): Ein Repositorium für standardisierte Pläne und Daten altägyptischer Architektur - Fauerbach, Ulrike (e-Forschungsberichte des DAI, 2023)
AEGARON publishes architectural data on ancient Egyptian monuments with newly developed uniform drawing standards and annotations. From published and unpublished material such as drawings, texts and photographs vector drawings are created and supplemented by a critical apparatus. Further information is provided by visiting and mapping the buildings on site. The archive includes building types from all regions and eras of Egypt up to the Middle Ages. The drawings and their critical apparatus are available for comparison and download with open access.